2005
DOI: 10.1073/pnas.0505845102
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene B 4 signaling through NF-κB-dependent BLT 1 receptors on vascular smooth muscle cells in atherosclerosis and intimal hyperplasia

Abstract: Leukotriene B4 (LTB4), a potent leukocyte chemoattractant derived from the 5-lipoxygenase metabolism of arachidonic acid, exerts its action by means of specific cell surface receptors, denoted BLT1 and BLT2. In this study, BLT1 receptor proteins were detected in human carotid artery atherosclerotic plaques, colocalizing with markers for macrophages, endothelial cells, and vascular smooth muscle cells (SMC). Challenge of human coronary artery SMC with either LTB 4 or U75302, a partial agonist that is selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
166
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(180 citation statements)
references
References 47 publications
11
166
0
3
Order By: Relevance
“…The important signaling through these receptors has been supported by findings in ApoE −/− mice with a targeted BLT 1 receptor, which have fewer SMCs in their lesions [38]. Furthermore, BLT receptor antagonism reduces intimal hyperplasia after vascular injury in rats [5,40]. Taken together, the LTinduced stimulation of SMCs suggests their involvement in the intimal hyperplasia associated both with early atherosclerosis and in-stent restenosis after coronary interventions [5].…”
Section: Intimal Hyperplasiasupporting
confidence: 49%
See 2 more Smart Citations
“…The important signaling through these receptors has been supported by findings in ApoE −/− mice with a targeted BLT 1 receptor, which have fewer SMCs in their lesions [38]. Furthermore, BLT receptor antagonism reduces intimal hyperplasia after vascular injury in rats [5,40]. Taken together, the LTinduced stimulation of SMCs suggests their involvement in the intimal hyperplasia associated both with early atherosclerosis and in-stent restenosis after coronary interventions [5].…”
Section: Intimal Hyperplasiasupporting
confidence: 49%
“…1) inhibits intimal hyperplasia after vascular injury in different animal models [5,39]. Recently, it was discovered that SMCs within human atherosclerotic lesions also express receptors for LTB 4 [38,40], mediating proliferation and migration of coronary artery SMCs [40]. The important signaling through these receptors has been supported by findings in ApoE −/− mice with a targeted BLT 1 receptor, which have fewer SMCs in their lesions [38].…”
Section: Intimal Hyperplasiamentioning
confidence: 61%
See 1 more Smart Citation
“…Many studies in vitro have shown that arachidonic acid metabolites influence on cell proliferation although the effects are cell-type specific [14][15][16][17]35]. Cysteinyl leukotrienes, products of the 5-LOX pathway, have been implicated in various stages of airway inflammation, in the present study, we found that inhibition of PLA 2 and 5-LOX significantly reduced the ASMC proliferation caused by platelets.…”
Section: Discussionsupporting
confidence: 66%
“…LTB 4 acting through its receptors (BLT1) can cause chemotaxis, degranulation, adhesion and enhance the survival of neutrophils. Although BLT1 was long known to be a neutrophil chemoattractant receptor, recent studies identified BLT1 expression on macrophages [22], smooth muscle cells [23], endothelial cells [24], activated T-cells [25] and mast cells [26] considerably expanding the potential role of LTB 4 . Recent experiments from our laboratory demonstrated functional expression of BLT1 on both mature and immature dendritic cells and having a direct effect in the control of adaptive immune responses [27].…”
Section: Leukotriene B 4 and Its Receptorsmentioning
confidence: 99%